2022
DOI: 10.1149/ma2022-0112850mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Graphene Oxide-Based Membranes: Viscoelastic Properties and Application to Broadband Microspeakers

Abstract: Graphene and graphene derivatives have attracted attention as materials for acoustic transduction [1-3]. Graphene oxide (GO) membranes and borate cross-linked graphene oxide (X-GO) membranes combine high stiffness, low mass density, and high loss coefficient. We show [4] that these mechanical properties are ideal for efficient, broadband, electro-acoustic transduction, where the acoustic diaphragm should be light, stiff, and internally damped. We present a quantitative comparison of the figure of merit, (E/ρ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In some cases, the synthesized GO diaphragms have Young's modulus exceeding 30 GPa, which can be further enhanced by cross-linking with borate ion, polyethylene imine, or other chemical groups to form cross-linked GO (X-GO) films, achieving a Young's modulus higher than 80 GPa. [112,119] Additionally, the unique viscoelastic properties of GO and X-GO result in a higher damping ratio compared to other traditional speaker diaphragms such as metal diaphragms. It is indicated that the damping ratio of microspeakers with GO and X-GO diaphragms is respectively 39% and 46% higher than those with aluminum diaphragms.…”
Section: Electrostatic Speakers Based On 2d Materials and Their Compo...mentioning
confidence: 99%
“…In some cases, the synthesized GO diaphragms have Young's modulus exceeding 30 GPa, which can be further enhanced by cross-linking with borate ion, polyethylene imine, or other chemical groups to form cross-linked GO (X-GO) films, achieving a Young's modulus higher than 80 GPa. [112,119] Additionally, the unique viscoelastic properties of GO and X-GO result in a higher damping ratio compared to other traditional speaker diaphragms such as metal diaphragms. It is indicated that the damping ratio of microspeakers with GO and X-GO diaphragms is respectively 39% and 46% higher than those with aluminum diaphragms.…”
Section: Electrostatic Speakers Based On 2d Materials and Their Compo...mentioning
confidence: 99%